Potential of Ulva lactuca and Sargassum duplicatum as Antihyperglycemic Agents in Type 2 Diabetes Mellitus - Aunurrahman, Muhammad Rezky Audia; Putri, Atina Rizki; Ishlahi, Salsabila Dinda Nuril; Putri, Radiah Meilani; Tito I.P.N, Anak Agung Bagus; Rizaldi, Muhammad Hilman; Dewi, Citranggana Prajnya (Jurnal Biologi Tropis, 2024)
Type 2 diabetes mellitus (DM) is a metabolic disease that occurs chronically and is characterized by elevated blood glucose levels. Current treatment of type 2 DM is with long-term oral hypoglycemic drug therapy, which is known to have side effects, such as kidney and liver disorders, so there is a need for drugs that have minimal potential side effects such as the use of Ulva lactuca and Sargassum duplicatum from seaweed. This paper will summarize the antihyperglycemic effects of Ulva lactuca and Sargassum duplicatum. The method used by researchers in this research is a literature study writing method that uses literature sources through Google Scholar and several credible websites such as Pubmed with the last 10 years of searches for articles and journals in Indonesian and English. The results of this study indicate that there is antidiabetic content in seaweed with Ulva lactuca and Sargassum duplicatum so that its use can be used as a complementary medicine. Therefore, treatment using seaweed with Ulva lactuca and Sargassum duplicatum has the potential to be developed to become a drug with minimal side effects in the treatment of type 2 DM in Indonesia.